Perancangan Mini Trainer Induktif Sensor Berbasis Arduino - Irma Yulia Basri; Dony Novaliendry; Intan Maisa Tania (Universitas Negeri Padang, 2022)
Sensor and Transducer is one of the subjects that must be followed by students of the Automotive Engineering Department, Faculty of Engineering, Padang State University, which weighs 2 credits. In accordance with the RPS for the Sensor and Transducer Course, there are several types of sensors that are the subject of study, one of which is an inductive sensor. Inductive sensor applications are applied in the automotive world such as Crankshaft Position Sensor (CKP), Camshaft Position Sensor (CMP), Vilocity Sensor. To make it easier to understand each sensor applied in the automotive world, students are required to master the basic concepts of the inductive sensor. One of the ways to increase student competence in the field of inductive sensors is the use of teaching aids during the learning process. Inductive sensor learning media in the Laboratory at the Automotive Engineering Department still uses analog processors, to support the development of digital technology today, so the authors provide an alternative by making teaching aids in the form of an Arduino-based Inductive Sensor Mini Trainer. This study uses the Research and Development (R&D) method which consists of Define, Design, Development, and Desseminate. The assembled inductive sensor mini trainer was tested for accuracy, and repeatibility test as well as feasibility test from media experts and users. The results of the research on the product trials carried out, obtained an accuracy level of 96.21%, the sensor output has linearity, the repeatibility test is obtained with an average of 0.1%. The level of product feasibility from Media Experts, is 94.68% and 96.23% from Respondents. So it can be concluded that the Inductive Sensor Mini Trainer is very suitable to be used as a learning medium.